Comparative Analysis of Direct Costs of Cancer and Risk Factors in Europe - Claudiu HERȚELIU; Alexandra HOROBEȚ; Vlad NERĂU; Anca (GHERMAN) PARASCHIV; George ȘTEFAN; Clara VOLINTIRU; Rodica Milena ZAHARIA; Marius GEANTĂ; Adriana Elena BOATA AZIS; Ramona POPESCU; Viktor SEMENOV; Lilia KRIACHKOVA; et al. (European Journal of Interdisciplinary Studies)
This study explores the direct costs and risk factors associated with cancer across European Union member states, emphasizing the economic and public health implications. A Cancer Risk Factors Index (CRFI) is developed to quantify and compare the impact of various determinants, including obesity, smoking, alcohol consumption, socioeconomic conditions, and pollution. Using data from Eurostat and other authoritative sources, we analyze the correlation between CRFI scores, healthcare expenditures, and cancer mortality rates. Results reveal significant disparities in cancer risk factors and healthcare investments across countries, with lower CRFI scores generally associated with higher healthcare spending and improved outcomes. The findings underscore the importance of comprehensive public health strategies and targeted interventions to address modifiable risk factors, reduce cancer-related mortality, and promote equitable healthcare access.